ANALISIS DAYA DUKUNG LAHAN BERDASARKAN TOTAL NILAI PRODUKSI PERTANIAN DI KABUPATEN GIANYAR - darma putra, i dewa gede agung; Utama, Made Suyana; Murjana Yasa, I.G. Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Indonesia’s sustainable national development is a series of sustainable efforts that covering all public life aspect, nation and Indonesia state. As a state which have many kind of biological, agriculture sector is dominant factor in sustaiable national development. This study aims to analyze of status of land support in Gianyar regency and to find out the effect of land support toward sector PDRB and contribution of PDRB agriculture sector in Gianyar regency in 2008 until 2012. The research type is quantitative descriptive by compare land availability with land need. Data has been used that is secondary data which obtained from statistic office in Gianyar regency. The data has been applied was agriculture commodity, PDRB percapita, PDRB agriculture sector in each subdistrict from year of 2008 until 2012. Then data processed by using calculation of land support and simple regression analysis to analyze land support toward agriculture production value total in Gianyar regency. The result showed that status of land support in Gianyar regency is deficit, it was caused by decrease of agriculture land that cause decrease of agriculture production. From analysis of simple regression obtained that land support have positive and significant effect toward PDRB agriculture sector and contribution of PDRB agriculture sector in Gianyar regency.
Keywords: Land Support, Agriculture Commodity, Land Conversion